Ganglioside Content of Human Platelets – Differences in Resting and Activated Platelets - Ferroni, Patrizia; Lenti, Luisa; Martini, Francesca; Ciatti, Filippo; Pontieri, Giuseppe M; Gazzaniga, Pier Paolo (Thrombosis and Haemostasis, 1997)
Gangliosides may play functional roles in platelet physiology, therefore this study has been designed to evaluate whether changes in ganglioside composition may occur as a consequence of platelet activation. The results obtained indicate that lactosylceramide and GM3 are the major glycosphingolipids of human platelets. The lipid-bound sialic acid (LBS A) content was 1.27 ± 0.04µεg/mg of protein. Resting platelets did not express GD3; GD3 was synthesized upon platelet activation (24 ± 8 ng/mg of protein). The stimulation of platelets with adenosine diphosphate showed the appearance of GD3 even in the absence of degranulation. Finally, incorporation of pyrene-labeled GM3 into platelet membranes, followed by stimulation with adenosine diphosphate, resulted in the appearance of a fluorescent band comigrating with GD3. The present studies indicate that sialyltransferase activation may occur as an early event following platelet stimulation, leading to GD3 synthesis mainly from the GM3 pool.